2020
DOI: 10.3390/su12030819
|View full text |Cite
|
Sign up to set email alerts
|

Revisiting a Water Conflict in Southeastern Oklahoma 6 Years Later: A New Valuation of the Willingness to Pay for Ecosystem Services

Abstract: In recent years, researchers have begun to adopt a perspective evaluating “winners and losers” regarding the consumption and value of ecosystem services. “Winners” tend to benefit from the ecosystem service and “losers” absorb most associated costs. Our study focuses on water use in Oklahoma (USA) and a plan to divert water from the Kiamichi River in southeastern Oklahoma for consumption at residences in the Oklahoma City metropolitan area. Our study is, in part, a follow-up from an initial 2013 survey of Okla… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
9
0
1

Year Published

2020
2020
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(13 citation statements)
references
References 41 publications
(98 reference statements)
0
9
0
1
Order By: Relevance
“…Because of the increase in the level of knowledge, the individual would be motivated to learn new things [61]. A study conducted in Oklahoma, USA found that culture is an effective determinant of the WTP for a sustainable ecosystem system [62]. Again, another study in China found that educated people showed more WTP for income derived from a sustainable ecosystem [25].…”
Section: Discussionmentioning
confidence: 99%
“…Because of the increase in the level of knowledge, the individual would be motivated to learn new things [61]. A study conducted in Oklahoma, USA found that culture is an effective determinant of the WTP for a sustainable ecosystem system [62]. Again, another study in China found that educated people showed more WTP for income derived from a sustainable ecosystem [25].…”
Section: Discussionmentioning
confidence: 99%
“…Conversely, this study finds that gender and education level of the tourists and local residents influence their choice preferences and, therefore, deduces that women give more importance to environment conservation (similar to [75,76]) and those with higher education have better awareness of sustainable development (similar to [77,78]). However, this phenomenon does not exist among aquaculture farmers.…”
Section: Discussion On Differences Of Respondentsmentioning
confidence: 56%
“…Education also appears to be crucial in affecting environmental WTP. Highly educated people show higher levels of concern about the environment [77,78]. Therefore, relevant preferential activities can be provided, such as teacher certificate discounts, postgraduate discounts, student discounts and women-related products, etc.…”
Section: Discussion On Differences Of Respondentsmentioning
confidence: 99%
“…Water resource management is of considerable importance in achieving sustainable human development, as water use takes many forms, including food production, health conditions, the security of domestic water supply and basic sanitation [64,65].…”
Section: Discussionmentioning
confidence: 99%